Serological study for chalamydiosis and Q fever in sheep and goat flocks with abortions - ΠΑΣΧΑΛΕΡΗ-ΠΑΠΑΔΟΠΟΥΛΟΥ Ε.; ΚΑΚΑΜΟΥΚΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
During the lambing season 1983- 1984 144 sheep and goat flocks with abortions were tested for chlamydiosis and Q fever. Complement fixation (CF) with antigen from local stran for chlamydiosis and from Boehring for Q fever was applied. Chamydia antibodies (titers over 1/32) were found in 65% of the 97 sheep flocks and 34% of the 47 goat flocks. Antibodies for Q fever (titers over 1/8) were found in 32% of the sheep flocks and 39% of the goat flocks. Antibodies to both agents were found in 21% of the sheep flocks and 26% of the goat flocks